2009
DOI: 10.1007/s10165-009-0197-6
|View full text |Cite
|
Sign up to set email alerts
|

Japan College of Rheumatology 2009 guidelines for the use of tocilizumab, a humanized anti-interleukin-6 receptor monoclonal antibody, in rheumatoid arthritis

Abstract: The introduction of biological agents targeting tumor necrosis factor-alpha (TNF-α) has brought about a paradigm shift in the treatment of rheumatoid arthritis (RA). Although these anti-TNF agents have excellent efficacy against RA, a substantial number of patients still show inadequate responses. In Western countries, such patients are already being treated with new classes of antirheumatic drugs such as abatacept and rituximab. Tocilizumab (TCZ) is a humanized monoclonal antibody developed in Japan against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 32 publications
1
83
0
3
Order By: Relevance
“…All guidelines with recommendations for anti-TNF therapy recommended screening for LTBI prior to initiation of anti-TNF therapy 16,22,23,25,26,30,33,53,54,55,56,57,58,59 . Seven guidelines commented on screening prior to ABAT 22,28,30,31,32,55,57 and 7 prior to TCZ 22,24,27,30,32,55,57 , and all recommended LTBI screening, although 5 guidelines highlighted that the magnitude of risk is unknown 22,24,27,30,55 . Eight guidelines commented on screening prior to RTX 22,29,30,31,32,55,57,60 .…”
Section: Recommendationmentioning
confidence: 99%
See 3 more Smart Citations
“…All guidelines with recommendations for anti-TNF therapy recommended screening for LTBI prior to initiation of anti-TNF therapy 16,22,23,25,26,30,33,53,54,55,56,57,58,59 . Seven guidelines commented on screening prior to ABAT 22,28,30,31,32,55,57 and 7 prior to TCZ 22,24,27,30,32,55,57 , and all recommended LTBI screening, although 5 guidelines highlighted that the magnitude of risk is unknown 22,24,27,30,55 . Eight guidelines commented on screening prior to RTX 22,29,30,31,32,55,57,60 .…”
Section: Recommendationmentioning
confidence: 99%
“…. Three guidelines recommended that IGRA could be considered as an alternative to TBST 22,24,27 , and 3 suggested that they may have a role, but their role is currently unclear 30,31,55 . Three guidelines suggested that they might have a role in patients who have received prior BCG vaccine 30,31,55 , with one guideline adding that they may also have a role in patients receiving immunosuppressants or in patients who have had prior non-TB mycobacterial infection 22 .…”
Section: Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…Также сходной c иФНО-α была структура инфекционных осложнений, которые включали Пн, флегмону, Herpes zoster-инфекцию, бактериальный артрит, реактивацию латентных инфекций, в т. ч. микобактериальных и т. д. В отдельных случаях СКИ приводили к летальному исходу. Эксперты Японской коллегии ревматологов полагают, что для минимизации развития оппортунистических инфек-ций у больных РА перед назначением ТЦЗ необходимо соблюдение следующих условий; а) число лейкоцитов периферической крови ≥ 4000/мм 3 , б) число лимфоцитов периферической крови ≥1000/мм 3 , в) отрицательный сывороточный тест на 1,3-бета-D-глюкан (маркер глубо-ких инвазивных микозов) [38].…”
Section: тоцилизумабunclassified